2013
DOI: 10.1002/emmm.201201783
|View full text |Cite
|
Sign up to set email alerts
|

Smurf2‐mediated degradation of EZH2 enhances neuron differentiation and improves functional recovery after ischaemic stroke

Abstract: EZH2 plays an important role in stem cell renewal and maintenance by inducing gene silencing via its histone methyltransferase activity. Previously, we showed that EZH2 downregulation enhances neuron differentiation of human mesenchymal stem cells (hMSCs); however, the underlying mechanisms of EZH2-regulated neuron differentiation are still unclear. Here, we identify Smurf2 as the E3 ubiquitin ligase responsible for the polyubiquitination and proteasome-mediated degradation of EZH2, which is required for neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 66 publications
6
87
0
Order By: Relevance
“…Consistent with a role of Stx on Pc stability in Drosophila development, proteasomal degradation has been reported to affect the stability of several PcG components in cultured vertebrate cells, including three PRC1 proteins BMI1, RING1B, and PHC, and one PRC2 protein EZH2 (Ben-Saadon et al, 2006;Maertens et al, 2010;Wu et al, 2010;Zaaroor-Regev et al, 2010;Sahasrabuddhe et al, 2011;Wu and Zhang, 2011;Yu et al, 2013). It is thus highly likely that protein degradation may play a general role in regulating PcG activity.…”
Section: Regulated Protein Degradation Plays a General Role In Modulamentioning
confidence: 84%
“…Consistent with a role of Stx on Pc stability in Drosophila development, proteasomal degradation has been reported to affect the stability of several PcG components in cultured vertebrate cells, including three PRC1 proteins BMI1, RING1B, and PHC, and one PRC2 protein EZH2 (Ben-Saadon et al, 2006;Maertens et al, 2010;Wu et al, 2010;Zaaroor-Regev et al, 2010;Sahasrabuddhe et al, 2011;Wu and Zhang, 2011;Yu et al, 2013). It is thus highly likely that protein degradation may play a general role in regulating PcG activity.…”
Section: Regulated Protein Degradation Plays a General Role In Modulamentioning
confidence: 84%
“…Another study reported that treatment of the DNA methylation inhibitor DZNep in 293T cells upregulates the ubiquitin ligase PRAJA1, which degrades EZH2 in vitro (41). Additionally, another study indicated that the SMAD ubiquitination regulatory factor 2 (Smurf2) is an E3 ubiquitin ligase responsible for the polyubiquitination and proteasome-mediated degradation of EZH2 in human mesenchymal stem cells (hMSCs) in vitro and in an intracranial xenograft model (42). These studies provide insights into the mechanism of EZH2 degradation through ubiquitination, mostly in normal somatic cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Smurf2 promotes senescence in fibroblasts, whereas in the nervous system Smurf2 may induce neuronal differentiation and promote neuronal polarization. [66][67][68] Whether sumoylation contributes to biological responses of Smurf2 besides EMT will be important to investigate in future studies.…”
Section: Discussionmentioning
confidence: 99%